Determinants of Eco-Friendly Product Adoption: The Role of Green Marketing, Environmental Awareness, and Price Perception in Shaping Consumer Decisions - Nabilah Rosa Azzahra; Zumrotul Fitriyah; Dewi Deniaty Sholihah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rise of environmental concerns has led to increasing interest in sustainable consumer behaviour, especially in urban retail settings. This study aims to examine the influence of green marketing, enviromental awareness, and price perception on consumers’ decisions to adopt eco-friendly products, specifically Ecobags, in the context of a modern retail environment. A quantitative approach was employed using purposive sampling, involving 105 respondents who had previously purchased Ecobags at Indomaret stores in Surabaya, Indonesia. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings reveal that while green marketing has a positive but statistically insignificant effect on purchase decisions, both environmental awareness and price perception significantly influence consumers' decisions to adopt eco-friendly alternatives. Environmental awareness emerged as the most influential factor, indicating that sustainability-driven knowledge and concern are key drivers of pro-environmental behavior. Additionally, consumers' perception of price as aligned with quality and benefit contributes significantly to their purchasing decisions. These results underscore the importance of enhancing sustainability messaging and optimizing pricing strategies to encourage widespread adoption of green products in emerging markets.